Mercury species in formerly contaminated soils and released soil gases - Sysalová, Jiřina; Kučera, Jan; Drtinová, Barbora; Červenka, Rostislav; Zvěřina, Ondřej; Komárek, Josef; Kameník, Jan (The Science of the total environment, 2017)
Total mercury (T-Hg), elemental mercury (Hg0), methylmercury (MeHg+), phenylmercury (PhHg+), and gaseous elemental mercury (GEM) species were determined in soils formerly contaminated by different processes from two sites in the Czech Republic. Analytical methods involved atomic absorption spectrometry (AAS) using a single-purpose Advanced Mercury Analyser AMA-254 and radiochemical neutron activation analysis (RNAA) for T-Hg determination, a thermal desorption method was used for Hg0 determination, gas chromatography coupled with atomic fluorescence spectrometry (GC-AFS) was employed for assay of MeHg+ and PhHg+, while GEM measurement was carried out using a portable Zeeman-AAS device Lumex RA-915+. The first sampling site was in the surroundings of a former PhHgCl-based fungicide processing plant next to Příbram (central Bohemia). Although the use of Hg-based fungicides as seed mordant have been banned, and their production stopped at the end of 1980's, highly elevated Hg contents in soil are still observed in the vicinity of the former plant, reaching T-Hg values >13mgkg-1. The second sampling site was an abandoned mining area named Jedová hora Hill near Hořovice (central Bohemia), where cinnabar (HgS) was occasionally mined as by-product of Fe ores hematite and siderite. Mining activities have been stopped here in 1857. Very high contents of T-Hg are still found at this site, up to 144mgkg-1. In most cases we found a statistically significant correlation between T-Hg and Hg0 values regardless of the pollution source. On the contrary, insignificant correlation was observed neither between T-Hg and GEM values, nor between GEM and Hg0. Concentrations of the investigated organomercury species were above a limit of detection (LOD) only in the most contaminated samples, where their levels were about two to three orders of magnitude lower compared to those of T-Hg.
Keywords: Elemental mercury; Phenylmercury; Gaseous elemental mercury; Total mercury; Methylmercury; Mercury contaminated soils